2016
DOI: 10.2527/jas.2016-0504
|View full text |Cite
|
Sign up to set email alerts
|

Monensin, virginiamycin, and flavomycin in a no-roughage finishing diet fed to zebu cattle1

Abstract: Two experiments were designed to evaluate the effects of monensin, virginiamycin, and flavomycin on growth performance, carcass characteristics, apparent total tract nutrient digestibility, and rumen fermentation of zebu cattle fed a no-roughage finishing diet (whole shelled corn [WSC] based). In Exp. 1, 100 crossbred bulls (; 392 kg [SD 46.8] average initial BW) were blocked by initial BW in a 101-d feedlot trial. Five treatments were evaluated using 4 pens per treatment (5 bulls/pen): monensin at 30 mg/kg DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
9
32
3
4
Order By: Relevance
“…No effect was observed in the carcass traits when the additives were combined. This result agrees with the study of Lemos et al (2016) which observed no effect of VM and MON association on carcass traits. Similarly, Silva et al (2004) suggested that the combination of VM and ionophores may have a synergistic effect on ADG, but without exerting substantial effects on carcass traits.…”
Section: Whole Study Period (0-110 Days)supporting
confidence: 93%
See 1 more Smart Citation
“…No effect was observed in the carcass traits when the additives were combined. This result agrees with the study of Lemos et al (2016) which observed no effect of VM and MON association on carcass traits. Similarly, Silva et al (2004) suggested that the combination of VM and ionophores may have a synergistic effect on ADG, but without exerting substantial effects on carcass traits.…”
Section: Whole Study Period (0-110 Days)supporting
confidence: 93%
“…This result agrees with the study of Lemos et al . () which observed no effect of VM and MON association on carcass traits. Similarly, Silva et al .…”
Section: Discussionmentioning
confidence: 81%
“…In experiments with feedlot calves, no differences were found for hot carcass weight or hot carcass yield of animals supplemented with virginiamycin (MONTANO et al, 2015;LEMOS et al, 2016;NAVARRETE et al, 2017). In a trial with feedlot sheep receiving 60: 40 concentrate: roughage ratio diets, treatments using banana pseudostem hay as roughage provided better results compared to those with Cynodon sp.…”
Section: Discussionmentioning
confidence: 89%
“…Rogers et al (1995) demonstrated, in a series of dose-response trials (19 mg to 27 mg VM/kg DM) with steers and heifers, that VM enhanced the average daily gain (4.6%), and gain to feed ratio (3.6%). However, studies describing the effect of VM on meat traits are still limited in beef cattle (Lemos et al, 2016;Salinas-Chavira et al, 2009), and, to our knowledge, no previous study has described fatty acid profiles of meat from feedlot Nellore cattle supplemented with VM. The utilization of microbes that are directly fed to livestock, such as Megasphaera elsdenii, could be an alternative for antibiotics such as VM, by reducing ruminal accumulation of lactate (Counotte, Prins, Janssen, & Debie, 1981).…”
Section: Introductionmentioning
confidence: 99%